Wage Expectations in the Labor Market: Survey Evidence on Rationality - Leonard, Jonathan S. (The Review of Economics and Statistics, 1982)
Using a new set of directly observed wage expectations among firms, this paper finds that in general firms' forecasts fail the unbiasedness and efficiency requirements of weak-form rational expectations. These market participants consistently underestimate the wages they actually end up paying, and their expectations do not efficiently utilize the information in past realizations. The mean absolute forecast error of two percent compares with an error of only five percent if static expectations were held. The major source of wage fore-cast error seems to be errors in predicting demand, rather than in predicting supply or the general price level. Wage forecast errors are positively correlated across fields with distinct supply patterns, and are positively correlated with quantity forecast error. The properties of stochastically weighted expectations and the effectiveness of the wage and price controls of the early 1970's are also discussed.